2022
DOI: 10.1002/admi.202200327
|View full text |Cite
|
Sign up to set email alerts
|

LSPR‐Enhanced Pyro‐Phototronic Effect for UV Detection with an Ag–ZnO Schottky Junction Device

Abstract: automobile exhaust monitoring, missile tracking, fire monitoring, etc. [1][2][3][4] Generally, the performance of UV detector is strongly depended on the sensing materials, and the wide bandgap semiconductors, which include GaN, SiC, ZnO, MoS 2 , InSe, etc, [5][6][7][8][9] are the preferred candidates owing to the high selectivity for UV light. Among them, ZnO is a prior choice for fabricating UV photodetectors at room temperature owing to the high electron mobility, [10] suitable bandgap (3.37 eV), high excit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 55 publications
1
5
0
Order By: Relevance
“…The possible formation of Ag/ZnO and Ag/SnO Schottky junctions could also have a significant impact on the pyro-phototronic effect. 19 However, the dark current of the devices (Fig. 4(a)) is not suppressed with the formation of these Schottky barriers for the samples with Ag NPs confirming that this effect is less dominant in our samples.…”
Section: Resultssupporting
confidence: 56%
See 1 more Smart Citation
“…The possible formation of Ag/ZnO and Ag/SnO Schottky junctions could also have a significant impact on the pyro-phototronic effect. 19 However, the dark current of the devices (Fig. 4(a)) is not suppressed with the formation of these Schottky barriers for the samples with Ag NPs confirming that this effect is less dominant in our samples.…”
Section: Resultssupporting
confidence: 56%
“…Recently, it was demonstrated that the combination of metal gold (Au) or silver (Ag) nanoparticles (NPs) with ZnO-based PDs are promising for enhancing the UV PD performance through the coupling of the localized surface plasmon (LSP) and pyroelectric effects. [18][19][20][21] However, the effect of the inclusion of metal NPs on the performance of self-powered PDs for visible light detection has not been investigated yet. It is well known that plasmonic metal NPs have a strong effect on the visible light absorption.…”
Section: Introductionmentioning
confidence: 99%
“…Ag NPs LSPR enhancement. Unlike Au NPs, Ag itself has an absorption peak around 300 nm and does not require interband jumping to enhance the PDs' absorption in the UV range, so Ag NPs are more suitable for UV detection [142]. In addition to the difference in the location of the absorption peaks, another advantage of Ag NPs is the conversion of ZnO to p-type conductivity during the doping process, which allows the formation of n-ZnO/p-ZnO: Ag heterojunction PDs to meet special needs, such as selfpowered requirements, as reported by Ning [143].…”
Section: Zno-based Uv Pds Enhanced By the Precious Metal Lspr Effectmentioning
confidence: 99%
“…[335] To enhance the properties of ZnO-based PDs, the PPE of ZnO has been combined with the LSPR of Ag NPs. [336] The self-powered PD was composed of ZnO NWs and Ag NPs, and it can detect 325 nm UV light rapidly and effectively with a power density of 340 nW/ cm 2 . The best R and D * under the same UV light and power density were 8.82 × 10 −5 A/W and 4.9 × 10 10 Jones, respectively and the τres was reduced to 8.72 ms.…”
Section: Pds With Pyroelectric and Lspr Effectmentioning
confidence: 99%